Gender Inequality: A Case Study of Ward-16 Bharatpur Metropolitan City - Sharma, Sharada Devi (Research Nepal Journal of Development Studies, 2020)
The main reason behind inequality is access to less power which is a byproduct of illiteracy and less income. An illiterate female cannot counter for herself neither can she counters for her offspring (mostly girls). To find out the gender inequality, this study has been conducted in Ward-16of Bharatpur metropolitan city. With the use of census method, this study primarily focuses on the primary data taken in whole ward and the secondary data collected from other sources. In the total population of 17546, 9197 are female and remaining 8349 are male. The survey research designwas used whereas purposive and simple random sampling was followed to select the respondents. The study was conducted in Chitwan district. The finding of the research is that there is inequality in male and female population in ward 16 of Bharatpur Metropolitan City. This inequality can only be broken if the sphere of planning is strengthened so as to uproot the root of inequality. Equality measure being one of the most important indicator of development, the only way to achieve the sustainable development goal is to empower all the population present inside nation.